Polyacetal resin composition

By using high weight reduction magnesium stearate or aluminum stearate and stabilizer in polyacetal resin, the yellowing of the polyacetal resin composition is suppressed, and the mixing of polyacetal resin and metal powder is solved. The problem of unstable color tone is suitable for raw materials for powder injection molding.

CN119278235APending Publication Date: 2025-01-07MITSUBISHI GAS CHEM CO INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380042902.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-15
Filing Date
2023-06-14
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When the polyacetal resin is mixed and used with metal powder, the use of fatty acid metal salts such as calcium stearate will cause the polyacetal resin composition to turn yellow, affecting the stability of the tone.

Method used

The polyacetal resin composition is prepared by melt-kneading by using magnesium stearate or aluminum stearate with a weight reduction rate of more than 20% and is deactivated but unstable after copolymerization is completed. , add stabilizers to inhibit yellowing.

Benefits of technology

It effectively inhibits the yellowing of the polyacetal resin composition and improves the color tone, and is suitable for raw materials for small and complex products made of powder injection molding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153017130000151
    Figure BDA0005153017130000151
  • Figure BDA0005153017130000161
    Figure BDA0005153017130000161
Patent Text Reader

Abstract

The invention provides a polyacetal resin composition, a metal resin composition, and a method for producing the polyacetal resin composition. Provided is a polyacetal resin composition containing 100 parts by weight of a polyacetal resin (A) and 0.1-0.9 part by weight of a fatty acid metal salt (B) having a weight loss ratio of 20% by weight or more, the weight loss ratio being a weight loss ratio when the temperature is raised from normal temperature to 200 DEG C at 200 DEG C / min in atmospheric air and held at 200 DEG C for 60 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyacetal resin composition, and more particularly to a polyacetal resin composition for kneading with metal powder. In addition, the present invention relates to a metal resin composition containing the polyacetal resin composition and the metal powder, a method for producing the polyacetal resin composition, and a method for producing a powder injection molded product using the polyacetal resin composition as a binder resin composition. Background Art

[0002] In recent years, a powder injection molding method has been developed in which a mixed product obtained by kneading a binder resin composition and a metal powder is injection-molded to produce a metal molded product. The powder injection molding method is superior in terms of the degree of freedom of shape and material of the molded product and dimensional accuracy.

[0003] Polyacetal resin is widely used as an engineering plastic due to its mechanical properties, friction / wear characteristics, chemical resistance, heat resistance, or electrical properties. Since polyacetal resin is easily removed by combustion and the amount of residual ash can be reduced, it is also preferred as a binder resin composition for metal powder in powder injection molding.

[0004] Patent document 1 discloses a polyacetal resin composition comprising (A) 100 parts by mass of a polyacetal resin, (B) 0.005 to 0.2 parts by mass of a nitrogen-containing compound, and (C) 0.01 to 0.8 parts by mass of a fatty acid metal salt such as calcium stearate, wherein the ratio of the content of the fatty acid metal salt (C) to the content of the nitrogen-containing compound (B) is 1 to 15.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-041133

[0008] Patent Document 2: International Publication No. 2017 / 200069 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] When a polyacetal resin composition is kneaded with a metal powder (i.e., when used as a binder resin composition for metal powder), a step of adding a predetermined amount of a nitrogen-containing compound and a fatty acid metal salt to the polyacetal resin is performed to improve the thermal stability and fluidity of the kneaded body (metal resin composition) (Patent Document 1). However, it is known that the use of fatty acid metal salts such as calcium stearate significantly causes yellowing of the polyacetal resin composition (Patent Document 2).

[0011] In view of the above circumstances, it is required to suppress yellowing of a polyacetal resin composition containing a fatty acid metal salt and to improve the color tone.

[0012] Technical solutions for solving technical problems

[0013] The present invention includes the following aspects. [1]

[0015] A polyacetal resin composition comprises 100 parts by weight of a polyacetal resin (A) and 0.1 to 0.9 parts by weight of a fatty acid metal salt (B) having a weight reduction rate of 20% by weight or more, wherein the weight reduction rate is the weight reduction ratio when the temperature is increased from room temperature to 200°C at 200°C / min in air at atmospheric pressure and maintained at 200°C for 60 minutes. [2]

[0017] The polyacetal resin composition according to [1], wherein the fatty acid metal salt (B) is magnesium stearate having a weight reduction rate of 20% by weight or more, aluminum stearate having a weight reduction rate of 20% by weight or more, or a combination of the two. [3]

[0019] The polyacetal resin composition according to [1] or [2], wherein the polyacetal resin (A) has a melt flow rate of 40 to 100 g / 10 min (temperature 190° C., load 2.16 kg). [4]

[0021] The polyacetal resin composition according to any one of [1] to [3], comprising 0.14 to 0.6 parts by weight of the fatty acid metal salt (B). [5]

[0023] The polyacetal resin composition according to any one of [1] to [4], wherein the polyacetal resin (A) is a crude polymer of a polyoxymethylene copolymer in which a polymerization catalyst is deactivated after completion of copolymerization but unstable terminal groups are not stabilized. [6]

[0025] The polyacetal resin composition according to any one of [1] to [5], further comprising 0.01 to 1.0 parts by weight of one or more stabilizers. [7]

[0027] The polyacetal resin composition according to any one of [1] to [6], wherein the polyacetal resin composition is used for kneading with metal powder. [8]

[0029] A metal resin composition comprising the polyacetal resin composition according to any one of [1] to [7] and a metal powder (C). [9]

[0031] A method for producing a polyacetal resin composition for use in mixing with metal powders, comprising the steps of melt-mixing 100 parts by weight of a polyacetal resin (A) and 0.1 to 0.9 parts by weight of a fatty acid metal salt (B) having a weight loss rate of 20% or more to prepare the polyacetal resin composition.

[0032] The above weight reduction rate is the weight reduction ratio when the temperature is increased from room temperature to 200°C at 200°C / min in air at atmospheric pressure and maintained at 200°C for 60 minutes.

[0033] The fatty acid metal salt (B) is magnesium stearate having a weight reduction rate of 20% by weight or more, aluminum stearate having a weight reduction rate of 20% by weight or more, or a combination of the two.

[10]

[0035] A method for producing a powder injection molded product, comprising the steps of injecting a mixed body obtained by melt-kneading a metal powder and a binder resin composition into a mold,

[0036] The adhesive resin composition is the polyacetal resin composition described in any one of [1] to [7].

[0037] Effects of the Invention

[0038] According to the present invention, yellowing of the polyacetal resin composition can be suppressed and the color tone can be improved. In particular, the kneaded body of the polyacetal resin composition and metal powder (metal resin composition) of the present invention is suitable as a raw material for manufacturing small and / or complex products by powder injection molding. DETAILED DESCRIPTION

[0039] [Polyacetal resin composition]

[0040] The polyacetal resin composition of the present invention contains 100 parts by weight of polyacetal resin (A) and 0.1 to 0.9 parts by weight of fatty acid metal salt (B) with a weight loss rate of 20% or more. The fatty acid metal salt (B) is specifically magnesium stearate, aluminum stearate or a combination of the two with a weight loss rate of 20% or more.

[0041] The polyacetal resin composition of the present invention is a binder resin composition for metal powder (C) used for kneading with metal powder (C). The polyacetal resin composition may be in a solid state, a powder state, a strand state, a granular state, or a combination thereof. The polyacetal resin composition of the present invention is used by kneading with metal powder (C).

[0042] The method for producing the polyacetal resin composition of the present invention comprises the step of melt-kneading 100 parts by weight of a polyacetal resin (A) and 0.1 to 0.9 parts by weight of a fatty acid metal salt (B) having a weight loss rate of 20% or more. The fatty acid metal salt (B) is magnesium stearate having a weight loss rate of 20% or more, aluminum stearate having a weight loss rate of 20% or more, or a combination of the two. The melt-kneading step is performed at a temperature above the melting temperature of the polyacetal resin composition (usually above 180° C.) (under atmospheric pressure).

[0043] [Polyacetal resin (A)]

[0044] Polyacetal resin (A) is a polymer compound having an acetal bond: -O-CRH- (where R represents a hydrogen atom or an organic group) in a repeating unit, and is generally a polymer compound having an oxymethylene group (-OCH2-) in which R is a hydrogen atom as a main structural unit. Polyacetal resin (A) may be a copolymer (block copolymer) or a terpolymer containing one or more repeating structural units other than oxymethylene groups. In addition, polyacetal resin (A) may have not only a linear structure but also a branched or cross-linked structure generated by using a glycidyl ether compound, an epoxy compound, an allyl ether compound, etc. as a copolymer monomer and / or a terpolymer monomer. As structural units other than the oxymethylene group, for example, oxyalkylene groups having 2 to 10 carbon atoms and which may have a branch, such as oxyethylene groups (-OCH2CH2- or -OCH(CH3)-), oxypropylene groups (-OCH2CH2CH2-, -OCH(CH3)CH2- or -OCH2CH(CH3)-), oxybutylene groups (-OCH2CH2CH2CH2-, -OCH(CH3)CH2CH2-, -OCH2CH(CH3)CH2-, -OCH2CH2CH(CH3)-, -OCH(C2H5)CH2- or -OCH2CH(C2H5)-), are mentioned. Among them, oxyalkylene groups having 2 to 4 carbon atoms and which may have a branch, or oxyethylene groups (-OCH2CH2-) are preferred. The content of the comonomer (structural unit other than oxymethylene) in the polyacetal resin (A) is 0.1 to 20% by weight, 0.1 to 15% by weight, 0.1 to 10% by weight, 0.1 to 8% by weight, 0.1 to 6% by weight, 0.1 to 4% by weight, 0.1 to 2% by weight, 0.1 to 1% by weight, 0.5 to 15% by weight, 0.5 to 10% by weight, 0.5 to 8% by weight, 0.5 to 6% by weight, 0.5 to 4% by weight, 0.5 to 2% by weight, or 0.5 to 1% by weight, based on the weight of the polyacetal resin (A).

[0045] The polyacetal resin (A) may be a terminal-stabilized product or a terminal-unstabilized product. For example, the polyacetal resin (A) is a crude polymer of a polyoxymethylene copolymer in which the polymerization catalyst is deactivated after copolymerization but the unstable terminal groups are not stabilized.

[0046] The polyacetal resin (A) is preferably a copolymer of a cyclic acetal such as trioxane or tetraoxane and ethylene oxide or 1,3-dioxolane. For example, the polyacetal resin (A) is an acetal copolymer using 1,3-dioxolane as a comonomer.

[0047] The polyacetal resin (A) has a melt flow rate of 1 to 100 g / 10 min, 10 to 100 g / 10 min, 15 to 100 g / 10 min, 20 to 100 g / 10 min, 25 to 100 g / 10 min, 30 to 100 g / 10 min, 35 to 100 g / 10 min, 40 to 100 g / 10 min, 42 to 100 g / 10 min, 45 to 100 g / 10 min, 40 to 95 g / 10 min, 42 to 95 g / 10 min or 45 to 95 g / 10 min as measured in accordance with ASTM-D1238 (temperature 190° C., load 2.16 kg). Preferably, the polyacetal resin (A) has a melt flow rate of 30 to 100 g / 10 min, 40 to 100 g / 10 min or 45 to 95 g / 10 min.

[0048] The method for producing the polyacetal resin (A) is not particularly limited and can be produced by a known method. For example, the polyacetal resin (A) having methylene oxide and alkylene oxide having 2 to 4 carbon atoms as structural units can be produced by copolymerizing a cyclic acetal of methylene oxide such as a trimer (trioxane) or a tetramer (tetraoxane) of formaldehyde with a cyclic acetal containing alkylene oxide having 2 to 5 carbon atoms such as ethylene oxide, 1,3-dioxolane, 1,3,6-trioxane or 1,3-dioxepane.

[0049] For example, the polyacetal resin (A) can be obtained by bulk polymerization of a cyclic acetal of methylene oxide and a cyclic acetal containing an alkylene oxide having 2 to 5 carbon atoms as a comonomer using a polymerization catalyst. A reaction terminator can be used as needed for deactivation of the polymerization catalyst and the polymerization growth terminal. In addition, a molecular weight regulator can be used as needed to adjust the molecular weight of the polyacetal resin (A).

[0050] The types and amounts of the polymerization catalyst, reaction terminator and molecular weight modifier are not limited as long as the effects of the present invention are not impaired, and known polymerization catalysts, reaction terminators and molecular weight modifiers can be used appropriately.

[0051] The polymerization catalyst is, for example, a Lewis acid such as boron trifluoride, tin tetrachloride, titanium tetrachloride, phosphorus pentachloride, phosphorus pentafluoride, arsenic pentafluoride and antimony pentafluoride, or a coordination compound or salt compound of these Lewis acids; a protonic acid such as trifluoromethanesulfonic acid or perchloric acid; an ester of a protonic acid such as an ester of perchloric acid and a lower aliphatic alcohol; an anhydride of a protonic acid such as a mixed anhydride of perchloric acid and a lower aliphatic carboxylic acid; or triethyloxonium hexafluorophosphate, trityl hexafluoroarsenate, acetyl hexafluoroborate, a heteropolyacid or an acid salt thereof, an isopolyacid or an acid salt thereof, or a perfluoroalkylsulfonic acid or an acid salt thereof.

[0052] The reaction terminator is, for example, a trivalent organic phosphorus compound (such as triphenylphosphine), an amine compound, an alkali metal, an alkaline earth metal hydroxide, or a combination thereof. The molecular weight modifier is, for example, methylal, methoxymethylal, dimethoxymethylal, trimethoxymethylal, or oxymethylene di-n-butyl ether.

[0053] Furthermore, the polyacetal resin (A) may contain known additives such as antioxidants, heat stabilizers, colorants, nucleating agents, plasticizers, fluorescent whitening agents, lubricants, antistatic agents, ultraviolet absorbers, and light stabilizers as required.

[0054] [Metal salt of fatty acid (B)]

[0055] The fatty acid metal salt (B) is a fatty acid metal salt having a weight reduction rate of 20% by weight or more. The "weight reduction rate" is measured as follows. Using a thermal analyzer (e.g., thermal analyzer manufactured by TA Instruments: TGA550), the weight reduction ratio of (e.g., 4 mg) of the fatty acid metal salt (B) when the temperature is increased from room temperature (20°C) to 200°C at 200°C / min in air at atmospheric pressure and maintained at 200°C for 60 minutes is defined as the "weight reduction rate". For example, when the weight of the fatty acid metal salt (B) before heating is set to W0, and the weight of the fatty acid metal salt (B) when the temperature is increased from room temperature (20°C) to 200°C at 200°C / min in air at atmospheric pressure and maintained at 200°C for 60 minutes is set to W1, the weight reduction rate of the fatty acid metal salt (B) is (W0-W1) / W0×100 (weight %).

[0056] The fatty acid metal salt (B) is specifically magnesium stearate, aluminum stearate or a combination thereof having a weight reduction rate of 20% by weight or more. The upper limit of the weight reduction rate of the fatty acid metal salt (B) is not particularly limited, for example, the weight reduction rate of the fatty acid metal salt (B) is 20 to 80% by weight, 20 to 60% by weight, 20 to 55% by weight, 20 to 50% by weight, 22 to 55% by weight, 22 to 50% by weight or 22.7 to 49.7% by weight.

[0057] Alternatively, the weight reduction rate of the fatty acid metal salt (B) is 22.7 to 49.5% by weight, or 25 to 50% by weight.

[0058] The content of the fatty acid metal salt (B) contained in the polyacetal resin composition is 0.1 to 0.9 parts by weight relative to 100 parts by weight of the polyacetal resin (A). In addition, the content of the fatty acid metal salt (B) contained in the polyacetal resin composition is 0.1 to 0.8 parts by weight, 0.1 to 0.6 parts by weight, 0.1 to 0.5 parts by weight, 0.1 to 0.3 parts by weight, 0.1 to 0.2 parts by weight, 0.12 to 0.8 parts by weight, 0.12 to 0.6 parts by weight, 0.12 to 0.5 parts by weight, 0.12 to 0.3 parts by weight, 0.12 to 0.2 parts by weight, 0.14 to 0.9 parts by weight, 0.14 to 0.8 parts by weight, 0.14 to 0.6 parts by weight, 0.14 to 0.5 parts by weight, 0.14 to 0.3 parts by weight, 0.14 to 0.2 parts by weight, or 0.15 to 0.5 parts by weight.

[0059] Alternatively, the content of the fatty acid metal salt (B) contained in the polyacetal resin composition may be 0.5 to 0.9 parts by weight.

[0060] [Method for producing polyacetal resin composition]

[0061] The method for producing the polyacetal resin composition of the present invention includes a step of melt-kneading the polyacetal resin (A) and the fatty acid metal salt (B) (melt-kneading step). The melt-kneading can be performed using, for example, a Banbury mixer, a roll, a Brabender, a single-screw extruder or a twin-screw extruder or a kneader.

[0062] The conditions such as temperature and pressure of the melt kneading step can be appropriately selected in consideration of the conventionally known method for producing the polyacetal resin composition. For example, the melt kneading step can be performed at a temperature higher than the melting temperature of the polyacetal resin (A), preferably 180 to 240°C or 200 to 220°C.

[0063] The polyacetal resin composition can be prepared by melt-kneading the polyacetal resin (A) and the fatty acid metal salt (B) at once so that the polyacetal resin (A) and the fatty acid metal salt (B) finally have the above-mentioned contents. Alternatively, the polyacetal resin composition can be prepared by temporarily preparing a polyacetal resin composition containing a high concentration of the fatty acid metal salt (B), and then melt-kneading and diluting it with another polyacetal resin (A).

[0064] [Metal resin composition]

[0065] The metal resin composition of the present invention comprises the above-mentioned polyacetal resin composition and metal powder (C). The metal resin composition is manufactured by melt-kneading the above-mentioned polyacetal resin composition and metal powder (C). The melt-kneading step is carried out at a temperature above the temperature at which the polyacetal resin composition melts (usually above 180°C). The metal resin composition (kneaded body) can be in a solid, powdery, stranded or granular form.

[0066] The metal resin composition has a fluidity of 9 g / 10 min or more, particularly 10 g / min or more, when measured under the conditions of a temperature of 190° C. and a load of 10 kg according to ASTM-D1238. Preferably, the metal resin composition has a fluidity of 10 to 800 g / 10 min, 10 to 700 g / 10 min, 10 to 600 g / 10 min, 10 to 500 g / 10 min, 10 to 400 g / 10 min, 10 to 300 g / 10 min, 10 to 200 g / 10 min, 10 to 100 g / 10 min, 10 to 90 g / 10 min, 10 to 80 g / 10 min, 10 to 70 g / 10 min, 10 to 60 g / 10 min, or 10 to 50 g / 10 min.

[0067] In addition, the bending strain (%) of the metal resin composition is obtained by, for example, preparing a 12.7 mm × 63.5 mm × 3.2 mm thick molded sheet, using "Auto graph (registered trademark) AGS-X" manufactured by Shimadzu Corporation, and subjecting the molded sheet to a three-point bending test at a bending speed of 2 mm / min, and measuring the point with the maximum bending strength as the bending strain.

[0068] The metal resin composition has a bending strain of 0.8% or more, particularly 1.0% or more. Preferably, the metal resin composition has a bending strain of 1.0 to 12.0%, 1.0 to 10.0%, 1.0 to 9.0%, 1.0 to 8.5%, 1.0 to 8.0%, 1.0 to 7.0%, 1.0 to 6.0%, 1.0 to 5.0% or 1.0 to 4.5%.

[0069] [Metal powder (C)]

[0070] The metal of the metal powder (C) is iron, aluminum, magnesium, cobalt, zinc, copper, nickel, titanium, tungsten or a metal compound or metal alloy using these metals as a matrix. Preferably, the metal powder (C) is a powder of stainless steel (SUS), and the stainless steel is austenitic stainless steel (SUS300 series), ferrite and martensitic stainless steel (SUS400 series) or precipitation hardening stainless steel (SUS600 series). Precipitation hardening stainless steel (SUS600 series) is particularly preferred. It should be noted that the particle size (average particle size) of the metal powder (C) is not particularly limited and can be measured by electron micrographs or laser diffraction / scattering particle size distribution measurement, etc., and is 1 to 100 μm, 1 to 50 μm, 1 to 25 μm or 1 to 10 μm.

[0071] The content of the metal powder (C) in the metal resin composition is 60 to 95 wt%, 65 to 95 wt%, 70 to 95 wt%, 80 to 95 wt%, 85 to 95 wt% or 70 to 90 wt% based on the weight of the metal resin composition. In other words, the content of the polyacetal resin composition in the metal resin composition is 5 to 40 wt%, 5 to 35 wt%, 5 to 30 wt%, 5 to 20 wt%, 5 to 15 wt% or 10 to 30 wt%.

[0072] Alternatively, the content of the metal powder (C) in the metal resin composition is 60 weight % or more and less than 95 weight %, 65 weight % or more and less than 90 weight %, 70 weight % or more and less than 90 weight %, 60 to 85 weight %, 65 to 85 weight %, or 70 to 85 weight %, based on the weight of the metal resin composition.

[0073] In addition, "● to ▲" means more than ● and less than ▲. For example, 60 to 95 weight % means more than 60 weight % and less than 95 weight %.

[0074] [Method for producing powder injection molded products]

[0075] The method for producing a powder injection molded product of the present invention comprises the step of injecting a mixed body obtained by melt-kneading a metal powder (C) and a binder resin composition into a mold, wherein the binder resin composition is the above-mentioned polyacetal resin composition. In addition, the method may also comprise the step of heating the molded mixed body in a degreasing furnace or placing it in a gaseous acid to remove the binder resin composition; and the step of sintering the molded body in a sintering furnace to form a powder injection molded product.

[0076] [Optional Ingredients]

[0077] In the polyacetal resin composition, any additives other than the above-mentioned stabilizers, nucleating agents, mold release agents, fillers, pigments, lubricants, plasticizers, ultraviolet absorbers, flame retardants or flame retardant aids may be added as needed within the scope that does not impair the purpose of the present invention. For example, as the arbitrary additives, there are glass fibers, glass flakes, glass beads, wollastonite, mica, talc, boron nitride, calcium carbonate, kaolin, silica, clay, asbestos, silicon dioxide, diatomaceous earth, graphite, molybdenum disulfide, glass fibers, intermediate fibers, potassium titanate fibers, boron fibers, carbon fibers, aramid fibers, potassium titanate whiskers, carbon black or pigments.

[0078] In one embodiment, the polyacetal resin composition of the present invention further contains 0.01 to 1.0 parts by weight, 0.01 to 0.7 parts by weight, 0.01 to 0.5 parts by weight, 0.01 to 0.3 parts by weight, 0.01 to 0.1 parts by weight, 0.1 to 0.5 parts by weight, or 0.1 to 0.3 parts by weight of one or more stabilizers, relative to 100 parts by weight of the polyacetal resin (A). The stabilizer includes an antioxidant, a heat stabilizer, or a combination thereof. The antioxidant is triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate, ethylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl) propionate, 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] or a combination thereof, preferably triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate. The heat stabilizer is melamine, methylol melamine, alkylated melamine, benzoguanamine, water-soluble melamine formaldehyde resin or a combination thereof, preferably melamine.

[0079] In one embodiment, the polyacetal resin composition of the present invention further contains 0.01 to 1.0 part by weight, 0.01 to 0.7 part by weight, 0.01 to 0.5 part by weight, 0.1 to 0.5 part by weight, or 0.1 to 0.3 part by weight of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate and 0.01 to 1.0 part by weight, 0.01 to 0.7 part by weight, 0.01 to 0.5 part by weight, 0.01 to 0.3 part by weight, or 0.01 to 0.1 part by weight of melamine.

[0080] Example

[0081] The following is a description of an example of the present invention. The materials used in the examples and comparative examples are as follows.

[0082] [Polyacetal resin (A)]

[0083] The polyacetal resin (A-1) used in Examples and Comparative Examples is an oxymethylene copolymer of trioxane and 1,3-dioxolane, and was prepared as follows.

[0084] To 100 parts by weight of trioxane were added 4.5 parts by weight of 1,3-dioxolane, a boron trifluoride diethyl ether complex added in the form of a benzene solution (0.62 mol / kg-benzene) as a catalyst in an amount of 0.06 mmol relative to 1 mol of all monomers, and methylal added in the form of a benzene solution (25 wt%) as a molecular weight modifier in an amount of 2000 ppm relative to all monomers, and continuous polymerization was carried out in a twin-screw kneader equipped with self-cleaning blades having a jacket set at a temperature of 65° C., so that the residence time in the polymerization machine was 15 minutes. A benzene solution of triphenylphosphine (25 wt%) was added to the produced polymer in an amount of 2 mol relative to 1 mol of the added boron trifluoride diethyl ether complex, and the resultant polymer was pulverized after the catalyst was deactivated to obtain a polyacetal resin (A-1) (polyacetal resin 1).

[0085] The polyacetal resin (A-2) used in the examples is an oxymethylene copolymer of trioxane and 1,3-dioxolane, and is prepared as follows.

[0086] To 100 parts by weight of trioxane were added 4.0 parts by weight of 1,3-dioxolane, a boron trifluoride diethyl ether complex added in the form of a benzene solution (0.62 mol / kg-benzene) as a catalyst in an amount of 0.06 mmol relative to 1 mol of all monomers, and methylal added in the form of a benzene solution (25 wt%) as a molecular weight modifier in an amount of 2500 ppm relative to all monomers, and continuous polymerization was carried out in a twin-screw kneader equipped with self-cleaning blades having a jacket set at a temperature of 65° C., so that the residence time in the polymerization machine was 15 minutes. A benzene solution (25 wt%) of triphenylphosphine was added to the produced polymer in an amount of 2 mol relative to 1 mol of the added boron trifluoride diethyl ether complex, and the resultant polymer was pulverized after the catalyst was deactivated to obtain a polyacetal resin (A-2) (polyacetal resin 2).

[0087] The melt flow rates of the polyacetal resins (A-1) and (A-2) were determined as follows.

[0088] To 100 parts by weight of the polyacetal resins (A-1) and (A-2), 0.3 parts by weight of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate (manufactured by BASF, trade name IRGANOX (registered trademark) 245) and 0.05 parts by weight of melamine (manufactured by Mitsui Chemicals, Inc.) as a stabilizer were added and mixed, and melt-kneading was carried out using a kneading machine "Labo Plastomill (registered trademark) 4C150" manufactured by Toyo Seiki Seisaku-sho, Ltd., under conditions of a set temperature of 220°C and a rotation speed of 30 rpm, and under a nitrogen flow (nitrogen flow rate of 5000 mL / min) for 20 minutes. The obtained product was pulverized, and the fluidity was measured using a melt indexer "L241" manufactured by Takara Industry Co., Ltd. in accordance with ASTM-D1238 under conditions of a temperature of 190°C and a load of 2.16 kg. The measurement results showed that the melt flow rate of the polyacetal resin (A-1) was 45 g / 10 min, and the melt flow rate of the polyacetal resin (A-2) was 88 g / 10 min.

[0089] [Metal salt of fatty acid (B)]

[0090] The fatty acid metal salt (B-1) was magnesium stearate "IMN" (magnesium stearate 1) manufactured by Dainichi Chemical Industry Co., Ltd. The weight loss rate of magnesium stearate 1 (B-1) was 49.7% by weight.

[0091] The fatty acid metal salt (B-2) was aluminum stearate "Aluminum Stearate 300" (Aluminum Stearate 1) manufactured by NOF Corporation. The weight loss rate of Aluminum Stearate 1 (B-2) was 22.7% by weight.

[0092] The fatty acid metal salt (B-3) was aluminum stearate "Aluminum Stearate 600" (Aluminum Stearate 2) manufactured by NOF Corporation. The weight loss rate of Aluminum Stearate 2 (B-3) was 28.5% by weight.

[0093] The fatty acid metal salt (B-4) was aluminum stearate "Aluminum Stearate 900" (Aluminum Stearate 3) manufactured by NOF Corporation. The weight loss rate of Aluminum Stearate 3 (B-4) was 25.7% by weight.

[0094] The fatty acid metal salt (B-5) was magnesium stearate "Technical Magnesium Stearate" (Magnesium Stearate 2) manufactured by NOF Corporation. The weight loss rate of Magnesium Stearate 2 (B-5) was 14.3% by weight.

[0095] The fatty acid metal salt (B-6) was magnesium stearate "Magnesium Stearate GP" (Magnesium Stearate 3) manufactured by NOF Corporation. The weight loss rate of Magnesium Stearate 3 (B-6) was 12.8% by weight.

[0096] The fatty acid metal salt (B-7) was magnesium stearate "M" (magnesium stearate 4) manufactured by Dainichi Chemical Industry Co., Ltd. The weight loss rate of magnesium stearate 4 (B-7) was 12.4% by weight.

[0097] [Metal powder (C)]

[0098] The metal powder (C) is SUS630 powder (average particle size: about 10 μm) manufactured by Epson Atmix Corporation.

[0099] [Example 1]

[0100] As shown in Table 1, the polyacetal resin composition of Example 1 was prepared by adding 0.3 parts by weight of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate (manufactured by BASF, trade name IRGANOX (registered trademark) 245) as a stabilizer, 0.05 parts by weight of melamine (manufactured by Mitsui Chemicals, Inc.) and 0.15 parts by weight of magnesium stearate (B-1) to 100 parts by weight of polyacetal resin (A-1), and melt-kneading was performed in a kneading machine "LaboPlastomill (registered trademark) 4C150" manufactured by Toyo Seiki Seisaku-sho, Ltd., at a set temperature of 220°C and a rotation speed of 30 rpm under a nitrogen flow (nitrogen flow rate of 100 mL / min) for 20 minutes. The polyacetal resin composition was pulverized using a pelletizer "Gran Cutter (registered trademark) SPC-400" manufactured by Hamo Co., Ltd. This was dried in an oven at 120° C. for 12 hours.

[0101] The metal resin composition of Example 1 is prepared by mixing 20 g of a polyacetal resin composition (10% by weight based on the weight of the metal resin composition) and 180 g of a metal powder (C) (90% by weight of the same standard) in a mixing machine "Labo Plastomill (registered trademark) 4C150" manufactured by Toyo Seiki Seisaku-sho Co., Ltd., at a set temperature of 180°C and a rotation speed of 60 rpm, and mixing under a nitrogen flow (nitrogen flow rate of 5000 mL / min) for 40 minutes and cooling and solidifying. In order to measure the bending strain properties and fluidity properties, the mixed body (metal resin composition) was crushed using a pelletizer "Gran Cutter (registered trademark) SPC-400" manufactured by Hamo Co., Ltd.

[0102] [Examples 2 to 23]

[0103] As in Example 1, the polyacetal resins (A-1, A-2) and triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate (manufactured by BASF, trade name IRGANOX (registered trademark) 245) as a stabilizer, 0.3 parts by weight, 0.05 parts by weight of melamine (manufactured by Mitsui Chemicals, Inc.), and the types and amounts (parts by weight) of fatty acid metal salts (B-1 to B-4) shown in Table 1 were melt-kneaded to prepare the polyacetal resin compositions of Examples 2 to 23.

[0104] The metal resin compositions of Examples 2 to 17 were prepared in the same manner as in Example 1 by containing 20 g of a polyacetal resin composition (10% by weight based on the weight of the metal resin composition) and 180 g of a metal powder (C) (90% by weight based on the same standard). In addition, the metal resin compositions of Examples 18 to 23 were prepared in the same manner as in Example 1 by containing 60 g of a polyacetal resin composition (30% by weight based on the weight of the metal resin composition) and 140 g of a metal powder (C) (70% by weight based on the same standard).

[0105] [Comparative Examples 1 to 9]

[0106] In the same manner as in Example 1, polyacetal resin compositions of Comparative Examples 1 to 9 were prepared according to the polyacetal resin (A-1) shown in Table 2, 0.3 parts by weight of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate (manufactured by BASF, trade name IRGANOX (registered trademark) 245) as a stabilizer, 0.05 parts by weight of melamine (manufactured by Mitsui Chemicals, Inc.), and the types and amounts (parts by weight) of fatty acid metal salts (B-1, B-5 ​​to B-7).

[0107] The metal resin compositions of Comparative Examples 1 to 7 were prepared in the same manner as in Example 1 by containing 20 g of a polyacetal resin composition (10% by weight based on the weight of the metal resin composition) and 180 g of a metal powder (C) (90% by weight of the same standard). In addition, the metal resin compositions of Comparative Examples 8 and 9 were prepared in the same manner as in Example 1 by containing 60 g of a polyacetal resin composition (30% by weight based on the weight of the metal resin composition) and 140 g of a metal powder (C) (70% by weight of the same standard).

[0108] The weight reduction rate of the fatty acid metal salts B-1 to B-7, the color tone (b value) of the polyacetal resin composition, and the bending strain and fluidity characteristics of the metal resin composition determined by thermogravimetric analysis were measured as follows.

[0109] [Measurement method and evaluation method]

[0110] (1) Thermogravimetric analysis of fatty acid metal salts

[0111] The device used for the thermogravimetric analysis of the fatty acid metal salt (B) was a thermal analyzer TGA550 manufactured by TA Instruments. 4 mg of the fatty acid metal salt (B) as a sample was heated from room temperature (20°C) to 200°C at 200°C / min in air at atmospheric pressure and maintained at 200°C for 60 minutes, and the weight reduction ratio at this time was defined as the "weight reduction rate".

[0112] The weight reduction rate of each fatty acid metal salt (B-1 to B-7) was determined.

[0113] (2) Color tone of polyacetal resin composition

[0114] The pulverized polyacetal resin composition was formed into a plate using "C, Mobile Type 0813" manufactured by EPSON TCFORM CORPORATION at a manifold temperature of 230°C and a barrel heater temperature of 220°C, and the color tone was evaluated using the plate. The color tone was evaluated by measuring the L, a, and b values ​​using a colorimeter "SE6000" manufactured by Nippon Denshoku Industries, and the b value was taken as the color tone value. The lower the b value, the lighter the yellow tone. In the present invention, the case where the b value is 4.0 or less is evaluated as yellowing is suppressed and the color tone is good.

[0115] (3) Bending strain

[0116] Using a desktop small injection molding machine "HAAKE MiniJet" manufactured by Thermo Fisher Scientific Co., Ltd., a 12.7mm×63.5mm×3.2mm thick molded sheet was made from the crushed mixed body (metal resin composition) at a barrel temperature of 220°C. Using "Auto graph (registered trademark) AGS-X" manufactured by Shimadzu Corporation, a three-point bending test was performed on the molded sheet at a bending speed of 2mm / min, and the point with the maximum bending strength was used as the bending strain (%). The bending strain value of the metal resin composition is preferably 1.0% or more.

[0117] (4) Liquidity

[0118] The fluidity of the pulverized kneaded body (metal resin composition) was measured using a melt indexer "L241" manufactured by Takara Industry Co., Ltd. in accordance with ASTM-D1238 at a temperature of 190°C and a load of 10 kg. The fluidity value of the metal resin composition is preferably 10 g / 10 min or more.

[0119] [Table 1]

[0120]

[0121] [Table 2]

[0122] [Table 2]

[0123]

[0124] As shown in Tables 1 and 2, the polyacetal resin compositions of Examples 1 to 23 all had b values ​​of 4.0 or less, yellowing was suppressed, and the hue was improved. On the other hand, the b values ​​of Comparative Examples 1 to 9 exceeded 4.0, and the hue was not improved.

[0125] In particular, the polyacetal resin compositions of Examples 1 to 15 and 18 to 21 not only have suppressed yellowing and excellent color tone, but also have preferable properties in terms of bending strain (1.0% or more) and fluidity (10 g / 10 min or more).

Claims

1. A polyacetal resin composition, characterized in that The invention comprises 100 parts by weight of a polyacetal resin (A) and 0.1 to 0.9 parts by weight of a fatty acid metal salt (B) having a weight reduction rate of 20% by weight or more, The weight reduction rate is a weight reduction ratio when the temperature is increased from room temperature to 200° C. at 200° C. / min in air at atmospheric pressure and then maintained at 200° C. for 60 minutes.

2. The polyacetal resin composition according to claim 1, characterized in that The fatty acid metal salt (B) is magnesium stearate having a weight reduction rate of 20% by weight or more, aluminum stearate having a weight reduction rate of 20% by weight or more, or a combination of the two.

3. The polyacetal resin composition according to claim 1 or 2, characterized in that The polyacetal resin (A) has a melt flow rate of 40 to 100 g / 10 min at a temperature of 190° C. and a load of 2.16 kg.

4. The polyacetal resin composition according to any one of claims 1 to 3, characterized in that The fatty acid metal salt (B) is contained in an amount of 0.14 to 0.6 parts by weight.

5. The polyacetal resin composition according to any one of claims 1 to 4, characterized in that The polyacetal resin (A) is a crude polymer of a polyoxymethylene copolymer which deactivates the polymerization catalyst after the copolymerization is completed but does not stabilize the unstable terminal groups.

6. The polyacetal resin composition according to any one of claims 1 to 5, characterized in that It also contains 0.01 to 1.0 parts by weight of one or more stabilizers.

7. The polyacetal resin composition according to any one of claims 1 to 6, characterized in that The polyacetal resin composition is used for mixing with metal powder.

8. A metal resin composition, characterized in that: The polyacetal resin composition according to any one of claims 1 to 7 and a metal powder (C) are contained.

9. A method for producing a polyacetal resin composition for use in mixing with metal powder, characterized in that: The method comprises the steps of melt-kneading 100 parts by weight of a polyacetal resin (A) and 0.1 to 0.9 parts by weight of a fatty acid metal salt (B) having a weight loss rate of 20% or more to prepare the polyacetal resin composition. The weight reduction rate is the weight reduction ratio when the temperature is increased from room temperature to 200°C at 200°C / min in air at atmospheric pressure and maintained at 200°C for 60 minutes. The fatty acid metal salt (B) is magnesium stearate having a weight reduction rate of 20% by weight or more, aluminum stearate having a weight reduction rate of 20% by weight or more, or a combination of the two.

10. A method for manufacturing a powder injection molded product, characterized in that: The method comprises the steps of injecting a mixed body obtained by melt-kneading a metal powder and a binder resin composition into a mold, The adhesive resin composition is the polyacetal resin composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polyacetal resin composition and metal resin composition

    JP2020041133A

  • Polyacetal resin composition and production process therefor

    WO2017200069A1